Problem Based Learning: An Effective Solution for Enhancing Conceptual Understanding of Simple Machines in Eighth Grade - Mustajab, Amin; Bahri, Samsul; Ayu Fatmala, Gista (Jurnal Pendidikan Fisika Undiksha, 2024)
This study discusses the effectiveness of the Problem-Based Learning (PBL) model in improving eighth-grade students' understanding of simple machines in the Natural Sciences (IPA) curriculum. Conducted at SMP Negeri 6 Satap Sekayam, the research employed a quantitative approach with a pre-experimental design involving 22 students. The results indicate that after the implementation of PBL, the average student score significantly increased from 73.81 to 92.32, reflecting an enhancement in conceptual understanding and application. Statistical analysis, including the Wilcoxon test, confirmed that the PBL model has a significant positive impact on students' conceptual understanding. These findings suggest that PBL promotes active engagement, collaboration, and deeper learning, making it a promising instructional strategy in physics education. Additionally, PBL was found to enhance higher-order thinking skills, social skills, and students' readiness to face future challenges. While most students showed significant improvement, one student did not make progress, highlighting the need for individualized support. Overall, this study affirms the effectiveness of PBL in enhancing the quality of education and preparing students with essential life skills.